Graduates need good communication skills: what does that mean? - Roslee, Noor Amiera; Abdul Latif @ Bapoo, Lilisuriani (Kuliyyah of Languages and Management (KLM), IIUM, 2020)
Employers have often expressed their concern over graduates’ abilities to communicate. Good English communication skills have been said to be lacking among graduates today but what employers are specifically referring to by ‘communication skills” is still vague. Hence, a survey was carried out on Malaysian managers from various industries to find out if grammatical accuracy is prioritized by employers. From the ninety eight responses received, it was discovered that accuracy is perceived to be important for both oral and written communication with grammatically correct writing being stressed to be very important in the workplace communication, in all sectors. In fact, half of the respondents expressed their reluctance to employ graduates who are unable to communicate with accurate English grammar. Based on these findings, it is recommended that the development of accuracy or correctness in using English in all workplace communication contexts is given priority in professional English language classrooms